ANTARA EFISIENSI ANGGARAN DAN KESENJANGAN KEPULAUAN: KETIMPANGAN TPACK DAN DISPARITAS REFLEKSI DIRI DALAM SIMULASI MENGAJAR VIRTUAL MAHASISWA PGSD UNIVERSITAS NUSA CENDANA - Chantika Seventin Desemberina Doke; Erna Bire; Firda Ariyani Amir; Maria Adelheid Wara Lay; Nadine Nelci Lidya Kuli; Gaudensius Jati Lamauran Koten; Hiwa Wonda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia’s budget and mobility efficiency policy under Presidential Instruction No. 1 of 2025, coupled with the urgency of fuel consumption reduction amid global energy price volatility, has pushed the full migration of Primary School Teacher Education (PGSD) microteaching simulations from face-to-face to fully virtual delivery. This shift raises the risk of unequal teaching-competence attainment, particularly for students from archipelagic regions with uneven telecommunications infrastructure such as East Nusa Tenggara (NTT). This study aims to identify the technical and pedagogical constraints faced by PGSD students at Universitas Nusa Cendana (Undana) in virtual teaching simulations, and to analyze the depth of their post-simulation self-reflection as a basis for formulating competence-enhancement strategies. Using a qualitative descriptive case study design, the study involved eight purposively selected students and three course lecturers, with data gathered through observation, in-depth interviews, and document study, analyzed using the Miles, Huberman, and Saldaña interactive model. Findings reveal three key patterns: a two-layered technical constraint (structural-geographic versus individually mitigable); a persistent imbalance within the TPACK framework, where technological and content competence—including generative AI fluency—outpaces pedagogical competence; and a marked disparity between the depth of orally elicited reflection and the shallower, more descriptive written reflection documents, indicating that current written reflection instruments underexploit students’ actual reflective capacity. The study recommends systemic, three-tiered intervention: institutional infrastructure reinforcement, curriculum reconstruction centered on the pedagogical domain of TPACK, and restructuring of self-reflection instruments around probing questions.